Knockdown of SOX18 inhibits the proliferation, migration and invasion of hepatocellular carcinoma cells - WANG, GUIMING (Oncol Rep, 2015)
Hepatocellular carcinoma (HCC) is one of the most common malignancies in the world. Recent studies have demonstrated that SOX18 is highly expressed in various types of cancer. In the present study, we found that SOX18 mRNA was overexpressed in HCC compared with non-tumorous tissues. We aimed to explore the effects of SOX18 siRNA on the proliferation, invasion and migration of two HCC cell lines, MHCC97H and HepG2, which overexpress SOX18. We found that SOX18 siRNA significantly inhibited the proliferation and induced cell cycle arrest at the G0/G1 phase. Results of the Transwell assay showed that the migration and invasion of the HCC cells were markedly impaired in the SOX18-knockdown cells. Gene set enrichment analysis (GSEA) showed that KEGG focal adhesion and chemokine signaling pathways were correlated with SOX18 expression. Furthermore, the mRNA and protein levels of RhoA, PDGFB, IGF1R, CCL2, CCL3 and CCL5 were decreased in the SOX18-knockdown cells. Importantly, we demonstrated that upregulation of SOX18 was associated with a poor outcome in HCC patients. These results indicate that SOX18 may serve as a prognostic factor and a promising therapeutic strategy for HCC.